Clinicopathologic features and treatment outcomes of patients with human epidermal growth factor receptor 2‐positive adenocarcinoma of the esophagus and gastroesophageal junction. Issue 3 (7th June 2012) - Phillips, B. E.; Tubbs, R. R; Rice, T. W.; Rybicki, L. A.; Plesec, T.; Rodriguez, C. P.; Videtic, G. M.; Saxton, J. P.; Ives, D. I.; Adelstein, D. J.
SUMMARY Human epidermal growth factor receptor 2 (HER2) is overexpressed in 21% of gastric and 33% of gastroesophageal junction (GEJ) adenocarcinomas. Trastuzumab has been approved for metastatic HER2‐positive gastric/GEJ cancer in combination with chemotherapy. This retrospective analysis was undertaken to better define the clinicopathologic features, treatment outcomes, and prognosis in patients with HER2‐positive adenocarcinoma of the esophagus/GEJ. Pathologic specimens from 156 patients with adenocarcinoma of the esophagus/GEJ treated on clinical trials with chemoradiation and surgery were tested for HER2. Seventy‐six patients also received 2 years of gefitinib. Baseline characteristics and treatment outcomes of the HER2‐positive and negative patients were compared both in aggregate and separately for each of the two trials. Of 156 patients, 135 had sufficient pathologic material available for HER2 assessment. HER2 positivity was found in 23%; 28% with GEJ primaries and 15% with esophageal primaries (P= 0.10). There was no statistical difference in clinicopathologic features between HER2‐positive and negative patients except HER2‐negative tumors were more likely to be poorly differentiated (P < 0.001). Locoregional recurrence, distant metastatic recurrence, any recurrence, and overall survival were also statistically similar between the HER2‐positive and the HER2‐negative groups, in both the entire cohort and in the gefitinib‐treated subset. Except for tumor differentiation, HER2‐positive and negative patients with adenocarcinoma of the esophagus and GEJ do not differ in clinicopathologic characteristics and treatment outcomes. Given the demonstrated benefit of trastuzumab in HER2‐positive gastric cancer and the similar incidence of HER2 overexpression in esophageal/GEJ adenocarcinoma, further evaluation of HER2‐directed therapy in this disease seems indicated.